A review on SF6 substitute gases and research status of CF3I gases. (November 2018) - Xiao, Song; Zhang, Xiaoxing; Tang, Ju; Liu, Siqi
Abstract: SF6 gas is widely used in electric power apparatus as an insulation and arc-quenching medium. However, the application of SF6 gas faces two serious problems, including the heavy global warming effect and high toxicity of its decomposition products. So, scholars committed to finding environmental-friendly alternative to SF6 gas and the relevant research results have been obtained. As an insulating or extinguishing medium, conventional gases, SF6 gas mixtures and electronegative gases and mixed gases exhibit different strengths and disadvantages. The current research progress of the main alternative gas has been summarized in this paper. And that is summarized in detail in terms of physical and chemical properties, insulating properties, arc characteristics, mechanism and the scope and limitations of different alternative gas in engineering applications are analyzed. Meanwhile, we forecast the development prospects of environment-friendly gas insulation, and theoretically analyzed CF3 I, which has the potential to replace SF6. Finally, we analyzed the current application feasibility and scope of CF3 I, and pointed out the further research direction.